PENGARUH PENERAPAN STRATEGI CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 8 BUKITTINGGI - Khairi, Umil; Aima, Zulfitri; Pratiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was conducted based on the facts showing that the students understanding on mathematical concept was still low and they were not accustomed to be involved in a discussion in class VIII of SMPN 8 Bukittinggi. This research was intended to see whether the use of Cooperative Integrated Reading and Composition (CIRC) strategy with quiz could improve the studentsâ understanding on mathematical concept better than that of the conventional learning. This was an experimental research which used random toward subject design. The instruments of the research were a quiz and a test on mathematical conceptual understanding. Based on the result of data analysis, it was revealed that the sample was normally distributed and homogeny. The result of hypothesis by examining t showed that P-value was less than Î±. This result indicated that the use of Cooperative Integrated Reading and Composition (CIRC) strategy with quiz could improve the studentsâ understanding on mathematical concept was better than that of the conventional learning.Â